Analisis Usaha Tani Pembibitan Kelapa Sawit Kelurahan Simpang Baru Kecamatan Tampan Di Kota Pekanbaru - Mariati '; Hainim Kadir; Rita Yani Iyan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aimed to determine of the cost of production, farm income of oil palm nursery of Topas and Marihat types and the average cost Marihat and Topas types. Population in this study is the Society of Oil Palm Nursery seek in Simpang Baru District, Tampan, Pekanbaru amounting to 30 families and the entire population in this study were sampled by census method. Analysis of the data used was descriptive and qualitative data analysis. From the research obtained the cost production of oil palm breeding farm of Marihat was Rp. 162 351 094 acres / year, the cost production of was Topas was Rp. 183 156 657 acres / year. The income of oil palm breeding farm of Marihat was Rp. 61,058,618acres / year, and for Topas was Rp. 184 152 657 acres/ year. the average cost of oil palm breeding farm of Marihat was Rp. 29580.28 acres / year,and for Topas was Rp.18.298.86 acres / year.Keywords: Oil Palm Breeding Farm, Revenue, Cost.